Struktur Modal Dan Nilai Perusahaan (Studi Pada Sektor Pertambangan Yang Terdaftar Di Bei Periode 2012-2015) - Murfat Effendi (LPPM University 17 Agustus 1945 Samarinda, 2017)
This study aims to describe the influence of capital structure to the firm value. Applying quantitative research, this study used secondary data taken from companies’ financial statements. The sampling technique applied was purposive sampling method. The population were mining companies listed in Indonesia Stock Exchange in the period of 2012-2015. In analyzing the data, this study applied classical assumption test and multiple linier regression. The indicators for the capital structure were Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), while the indicator for Firm Value was Tobin’s Q. The findings showed that there was a significant effect of the independent variables of DAR and DER simultaneously. Partially, DAR was significantly affected by Tobin’s Q while DER was not influenced by the dependent variable.